ANALYSIS OF THE CONTENTS OF TRAINING APPLIANCES AND METHODICAL MANUALS OF UKRAINIAN LANGUAGE FOR PRIMARY SCHOOL (1920-1941 YEARS) - Kachur, Alina M. (Educological discourse, 2014)
Under the conditions of formation of the system of education is particularly relevant problem - filling scientist subject. Content of education - a kind requirements model society in the preparation of the young generation. Material carrier content of the Ukrainian language as a school subject, for its implementation are teaching kits in the Ukrainian language. Therefore the development and creation of of textbooks and manuals, didactic of tables - a priority the development of the school. Article descriptive overview ABC books, textbooks Ukrainian language and demonstration materials, which are widely used in primary schools in Ukraine since the beginning of the reign of Soviet power and the beginning of the Great Patriotic War.